Impact of school feeding programmes on educational outcomes: Evidence from dry cereals in schools in Burkina Faso - Pouirkèta Rita Nikiema (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Food for Education (FFE) programmes have been implemented in developing countries since the 1960s. This paper examines the impact of the Catholic Relief Services (CRS) school feeding programme on pupils' attendance and girls' enrolment rate within primary schools in northern Burkina Faso. Using difference-in-difference (DID) estimation with the data set on the Beoog Biiga programme, we find that take-home rations (THRs) increased school attendance for both boys and girls. Moreover, the findings show that girls' enrolment rate within schools increased by 3.2 per cent. This is driven by the increase in the number of newly enrolled girls compared with boys. We conclude that THRs have the potential to increase girls' educational attainment and gender equality within schools.
Keywords: D04; I21; I25; O15; 330; school feeding programme; take home ration; enrolment; attendance; Burkina Faso